Proses Manajemen Kinerja di SMP Swasta Muhammadiyah 02 Medan - Fella Annisa Harahap; Tasya Zuraira; Intan Ramadani; Sri Apulina; Imam Amirmusthofa; Aswaruddin Aswaruddin; Tegar Jaya Putra (Jurnal Publikasi Ilmu Manajemen, 2024)
The performance management process which consists of planning, monitoring and assessing performance in schools has a crucial role in improving the quality of education. This article aims to analyze the performance management process carried out at SMP Swasta Muhammadiyah 02 Medan Medan. The research method used in this article is qualitative by collecting data through interviews with informants. The results of the interviews conducted showed: 1) Planning includes curriculum development strategies, resources and school policies. 2) Monitoring focuses on evaluating the learning process, classroom management, and student engagement. 3) Meanwhile, performance assessment helps measure student achievement, teaching effectiveness, and achievement of school goals. The synergy of these three aspects creates an adaptive and progressive educational environment. By implementing careful planning, continuous monitoring, and holistic performance assessment, schools can ensure optimal development of student potential, respond to changing educational dynamics, and ensure sustainable learning quality.